Perancangan Jaringan LTE (Long Term Evolution) Indoor Di Gedung C Fakultas Teknik Universitas Riau - Triyanti, Triyanti; Febrizal, Febrizal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This paper purposes LTE (Long Term Evolution) network design using indoor system in the area of Gedung C faculty of engineering, Universitas Riau. The design was involved several stages namely data analysis based on link budget and COST 231 Multiwall, network planning based on coverage (coverage planning), network planning base on capacity (capacity planning) and the final stage of desain to do simulation using the software RPS 5.4 (Radio Propagation Simulator). This simulation using two scenarios, the first using calculation coverage planning obtained 9 antenna and second scenario using calculation of capacity planning obtained 6 antenna. Base on simulation, the best scenario is capacity planning with obtained parameters of the Receive Signal Level (RSL) at -63.65 dBm, while the value of Signal Interface Ratio (SIR) obtained is 21.02 dB.Keywords : LTE, Coverage, Capacity, Link Budget, RSL, SIR and COST 231 Multiwall